Pemahaman Remaja tentang Kesehatan Reproduksi Ditinjau dari Jenis Kelamin di MTsN 2 Agam - Nilta Putri; Sri Hartati (YASIN, 2026)
Adolescent reproductive health is an important aspect of student development; however, studies examining gender-based differences in reproductive health understanding among madrasah students remain limited. This study aimed to analyze differences in reproductive health understanding between male and female adolescents at MTsN 2 Agam. The study employed a quantitative approach with a comparative descriptive design and involved 136 students, comprising 69 male and 67 female students, who were selected through proportionate stratified random sampling. Data were collected using a closed-ended questionnaire on reproductive health understanding that met the validity and reliability criteria. The data were analyzed using descriptive statistics and an independent-samples t-test with the assistance of IBM SPSS Statistics. The results showed that most students were classified in the understanding category of reproductive health knowledge, comprising 103 respondents (75.7%). The test results also indicated a significant difference in reproductive health understanding between male and female students (p < .001). Female students had a higher mean understanding score (M = 166.79) than male students (M = 155.04). These findings strengthen the evidence that gender is associated with variations in adolescents’ levels of reproductive health understanding. This study emphasizes the importance of strengthening reproductive health education that is responsive to students’ needs. In practical terms, the results can serve as a basis for madrasahs and guidance and counseling teachers to design comprehensive reproductive health education programs appropriate to students’ characteristics. Future research should consider the roles of family, the social environment, and digital media in shaping adolescents’ reproductive health understanding.